Русинський рух у сучасній Румунії: ідентифікація, структура, рефлексії - Зан, М. (Народна творчість та етнологія, 2011)
In the article considered the evolution of the Ruthenian movement in modern Romania, who went public and political arena in the country at the beginning of the XXI century. According to the results of population census 2002 found out the specifics of Rusyn identity. The questions of parliamentary representation of Rusyns analyzed through the public activity of Gheorghe Firczak and Cultural Union of Rusyns in Romania. The ambiguous evaluations of Ruthenian movement in ethnographic field of Maramureş County are illustrated. The author concludes amorphous of Ruthenian movement in Romania compared to the Prešov Region or Transcarpathia and disparity of mobilization (situational) vector of its leaders and primordial (Ukrainian) essence of his «unconscious recipients».